Therapeutic Implications of Epidermal Growth Factor Receptor (EGFR) in the Treatment of Metastatic Gastric/GEJ Cancer - Adashek, Jacob J.; Arroyo-Martinez, Yadis; Menta, Arjun K.; Kurzrock, Razelle; Kato, Shumei (Frontiers in Oncology, 2020)
Gastric cancer remains third leading cause of global cancer mortality and is the fifth most common type of cancer in the United States. A select number of gastric cancers harbor alterations in EGFR and/or have amplification/overexpression in the HER2; 2-35% and 9-38%, respectively. The advent of next-generation sequencing of tissue and circulating tumor DNA has allowed for the massive expansion of targeted therapeutics to be employed in many settings. There have been a handful of trials using EGFR inhibitors with modest outcomes. Using novel strategies to target multiple co-mutations as well as identifying immunoregulatory molecule expression patterns will potentially drive future trials and improve gastric cancer patient outcomes.